A comparative study of the harms of nitrous oxide and poppers using the MCDA approach. (September 2022) - Ferreira, Plinio M; Winstock, Adam R; Schlag, Anne Katrin; Brandner, Brigitta; Henderson, Graeme; Miller, Ian; van Amsterdam, Jan; Phillips, Lawrence D; Taylor, Polly; Gittins, Rosalind; Rolles, Steve; Brink, Wim van den; et al.
The recent surge in recreational (non-medical) use of nitrous oxide (N2 O, also known as 'laughing gas') often by inhaling it from balloons, has attracted the attention of some politicians with calls to control its possession under the United Kingdom (UK) Misuse of Drugs Act 1971 (currently selling, but not possession, for recreational use is controlled under the Psychoactive Substances Act 2016). Meanwhile, the recreational use of nitric monoxide (NO) as delivered by alkyl nitrites, also known as 'poppers' has also raised concerns, but unlike N2 O, its use was not controlled under the 2016 Act. To inform future-decision making processes and ensure that any such decisions are based on the best evidence, Drug Science conducted a Multi-Criteria Decision Analysis (MCDA) about N2 O and poppers to compare the overall harms of these two drugs to the harms of 20 drugs previously evaluated and published by Nutt et al. The group assessed harm scores for N2 O and poppers on the original 16 harm criteria using the associated 0 to 100 scales, on each of which 100 had been assigned to the most harmful drug and zero to the least harmful, though that often meant no harm. On the overall harm scale, N2 O scored 6, just above magic mushrooms (psilocybin) while 'poppers' scored 5. Together these are the three lowest drugs on the overall harm scale. Although their overall scores are similar, the reasons behind the ratings differ. Nitrous oxide was considered more harmful than poppers for Dependence, Environmental Damage, Drug Related Relative Impairment of Mental Functioning, and Family Adversities, while poppers are more harmful than N2 O for Injury, Drug Related Damage, Economic Cost, and Drug Related Mortality. When assessing the risk different substances may hold when making policy decisions, it is important to acknowledge the relative contribution of these diverse harms within different domains.